2012
DOI: 10.1111/j.1467-9566.2012.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of nonsense: experiences of mild cognitive impairment

Abstract: Alzheimer's disease (AD) is a stigmatised condition popularly assumed to be a death sentence for diagnosed individuals. Consequently, people with AD are often deemed incapable (and perhaps unworthy) of contributing to the social discourse surrounding their illness experience. Data from qualitative interviews with 18 people diagnosed with the potential precursor of AD known as mild cognitive impairment (MCI) are examined. Using grounded theory methods, analysis revealed overarching themes of uncertainty concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
129
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(132 citation statements)
references
References 59 publications
3
129
0
Order By: Relevance
“…The ambiguity and uncertainty of the diagnosis [30] cause many patients to desire more information about their condition, such as how it differs from “normal” aging and how it differs from dementia [31]. Amyloid imaging may allow a physician to give the patient additional information about potential causes of their MCI, improve prognostic information, and reduce the ambiguity and uncertainty associated with the diagnosis [29, 30, 32–34]. Although some patients may want this information, others may express a desire “not to know” [35].…”
Section: Recommendationsmentioning
confidence: 99%
“…The ambiguity and uncertainty of the diagnosis [30] cause many patients to desire more information about their condition, such as how it differs from “normal” aging and how it differs from dementia [31]. Amyloid imaging may allow a physician to give the patient additional information about potential causes of their MCI, improve prognostic information, and reduce the ambiguity and uncertainty associated with the diagnosis [29, 30, 32–34]. Although some patients may want this information, others may express a desire “not to know” [35].…”
Section: Recommendationsmentioning
confidence: 99%
“…An expert Amyloid Imaging Taskforce sponsored by the Alzheimer’s Association and the Society of Nuclear Medicine and Molecular Imaging developed Appropriate Use Criteria for amyloid PET, which outlined patients with persistent or progressive mild cognitive impairment (MCI), patients with possible AD due to atypical or mixed etiology presentation, and patients with young-onset dementia as appropriate for amyloid imaging [11]. Amyloid imaging may identify MCI patients at increased risk for progression to AD dementia [12, 13] and reduce ambiguity from a clinical diagnosis that is associated with substantial uncertainty [1416]. It may help clinicians distinguish AD from other causes of dementia, especially in patients with atypical presentations [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…The findings showed that the informants, as next of kin to dementia sufferers in an early stage of the disease, experienced life as a burden. This was the case because of, for example, feelings of isolation and worries about the future, which is also a known result from other studies 1,3,4. The findings highlight that next of kin to dementia sufferers need relief6 and support 4.…”
Section: Discussionmentioning
confidence: 51%
“…This can be explained by the fact that there is no cure for dementia2 and the knowledge that the disease is going to get worse, both of which give a feeling of fear to those with dementia3 and to their next of kin. Because of uncertainty about the prognosis and the future,4 next of kin need information and support during the disease process.…”
Section: Introductionmentioning
confidence: 99%